Determination of features of formation of energy supply systems with the use of renewable energy sources in the transition period - Nakashydze, Liliya; Gabrinets, Volodimir; Mitikov, Yurii; Alekseyenko, Sergey; Liashenko, Iryna (Eastern-European Journal of Enterprise Technologies, 2021)
An urgent scientific and practical problem is the formation of energy efficient systems for ensuring climatic conditions in premises based on the use of renewable energy sources. The work has improved the technical and methodological approach to the calculations of energy supply and storage systems when using energy-active fences. The special effectiveness of these fences has been shown in the transitional periods of the year, that is, in spring and autumn. A mathematical model has been developed to reliably predict the process of ensuring temperature comfortable conditions (heat balance) when using nonparametric statistics methods. It will improve the quality of forecasting the effect of external air temperature during the transitional periods of the year. The temperature inside the room is taken into account in the presence of a multilayer energy-active fence. To determine the approach to the use of heat in energy supply systems during the transition period, thermal parameters from the inner and outer sides of the building structure are considered. This makes it possible to take into account changes in the heat transfer of these structures when designing a power supply system and determining the optimal modes of its functioning in various natural conditions. The function of energy-active fences associated with the generation of additional heat into the system, obtained through the conversion of solar radiation energy, is considered. To increase this generation, special multilayer designs of energy-active fencing have been proposed. The proposed thermal modernization with the use of energy-active fences allows, on average, over the cold period of the year, to reduce energy consumption by 3.5 times for industrial and residential buildings